2021
DOI: 10.3390/jcm10194307
|View full text |Cite
|
Sign up to set email alerts
|

Role of Janus Kinase Inhibitors in Therapy of Psoriasis

Abstract: Janus kinases inhibitors are molecules that target Janus kinases—signal transducers and activators of transcription (JAK/STAT). They inhibit this intracellular signal pathway, blocking the gene transcription of crucial proinflammatory cytokines that play a central role in the pathogenesis of many inflammatory and autoimmune diseases, including psoriasis. This process reduces psoriatic inflammation. The JAK inhibitors are divided into two generations. The first generation of JAK inhibitors blocks two or more di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 78 publications
1
32
0
2
Order By: Relevance
“…The favorable response to Baricitinib in this patient appears to support our hypothesis. In addition, clinical trials of Baricitinib have shown encouraging effects without serious side effects in treatment of various other autoimmune skin diseases including psoriasis, 14,15 which is in line with the results of our case. Other benefits of Baricitinib include its easy oral administration and lower cost compared to other intravenous/ subcutaneous agents which are invasive and more expensive.…”
Section: Discussionsupporting
confidence: 91%
“…The favorable response to Baricitinib in this patient appears to support our hypothesis. In addition, clinical trials of Baricitinib have shown encouraging effects without serious side effects in treatment of various other autoimmune skin diseases including psoriasis, 14,15 which is in line with the results of our case. Other benefits of Baricitinib include its easy oral administration and lower cost compared to other intravenous/ subcutaneous agents which are invasive and more expensive.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, there are no FDA-approved JAK inhibitors in the treatment of psoriasis, however, oral tofacitinib is approved for psoriatic arthritis. Oral tofacitinib, is a JAK1 and JAK2 inhibitor and is the most studied oral JAK inhibitor in moderate to severe plaque psoriasis ( Table 6 ) [ 108 ]. Deucravacitinib, formerly known as BMS986165, is an oral selective TYK2 inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…JAK inhibitors are also an emerging class of small molecule inhibitors, and oral tofacitinib is the most studied oral JAK inhibitor in psoriasis [ 108 , 111 , 112 ]. Although JAK inhibitors present a new small molecule inhibitor with efficacy in psoriasis, it is associated with numerous black box warnings, and careful consideration must be used when opting for these medications [ 55 , 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…In late stages of clinical development is the TYK2 inhibitor deucravacitinib, which in clinical trials offers quite convincing clinical effects with a good safety profile. The background for the latter development is the recognition that many mediators, for example type I interferons or IL-23, mediate their inflammatory signals via Janus kinases (JAK, to which TYK2 also belongs) ( 85 , 86 ). Thus, by blocking these signaling molecules, an (indirect) inhibition of inflammatory mechanisms can be achieved.…”
Section: Chronic Inflammatory Skin Diseasesmentioning
confidence: 99%